Apoptosis and 1-methyl-2-nitroimidazole toxicity in CHO cells. - Brezden, C. B. (Nature Publishing Group, 1997)
The time course and characteristics of the selective hypoxic cytotoxicity of the 2-nitroimidazole model compound 1-methyl-2-nitroimidazole (INO2) were analysed during prolonged time periods (up to 5 days post treatment). When control populations were seeded at the same cell density as drug-treated cells, they entered confluency at day 3 and underwent apoptosis at day 5, which appeared to be mediated by an autocrine mechanism. In subsequent studies of drug-treated cells, the seeding density of treated cells was adjusted to avoid this cell confluency effect. Treatment with a low INO2 concentration (2.5 mM) resulted in apoptotic DNA fragmentation (ladders), which was observed 4-5 days after an acute 6-h hypoxic drug exposure. In contrast, at a high INO2 concentration (40 mM) for 2 h, which was equitoxic to the low concentration, no characteristic DNA ladders were observed. Fluorescence microscopy revealed apoptotic bodies and pyknotic nuclei 5 days following hypoxic 2.5 mM INO2 exposure, whereas 40 mM INO2 hypoxic treatment produced cellular ghosts devoid of DNA 5 days after exposure, consistent with the DNA ladder results. However, characteristic apoptotic morphology was previously observed immediately after the acute hypoxic exposure of 40 mM INO2. Cell cycle analysis and DNA fragmentation as measured by the TdT assay suggested that dose-dependent differences in the apoptotic response occur post exposure after an equitoxic acute hypoxic exposure to either the low or the high INO2 concentration. This dose-dependent differential in response may be attributed to the degree of initial DNA damage as measured by the comet assay. IMAGES: